Health Care Communication Laws in the United States, 2013: Implications for Access to Sensitive Services for Insured Dependents. Issue 2 (March 2017) - Kristoff, Iris; Cramer, Ryan; Leichliter, Jami S.
Abstract : Young adults may not seek sensitive health services when confidentiality cannot be ensured. To better understand the policy environment for insured dependent confidentiality, we systematically assessed legal requirements for health insurance plan communications using WestlawNext to create a jurisdiction-level data set of health insurance plan communication regulations as of March 2013. Two jurisdictions require plan communications be sent to a policyholder, 22 require plan communications to be sent to an insured, and 36 give insurers discretion to send plan communications to the policyholder or insured. Six jurisdictions prohibit disclosure, and 3 allow a patient to request nondisclosure of certain patient information. Our findings suggest that in many states, health insurers are given considerable discretion in determining to whom plan communications containing sensitive health information are sent. Future research could use this framework to analyze the association between state laws concerning insured dependent confidentiality and public health outcomes and related sensitive services. Abstract : Supplemental Digital Content is Available in the Text.